602 Specialty Training Progression from Core Surgical Training: Is There Evidence from Plastic Surgery of The Importance of Location, Location, Location?. (4th May 2021) - Vinnicombe, Z; Little, M; Johal, K
Abstract: Introduction: Obtaining a National Training Number (NTN) in Plastic Surgery is highly competitive (<40 posts per year), with applicant:post ratios between 3.73 to 4.19 in 2017-2019. Our aim was to compare deaneries for numbers successfully progressing directly from CT2 into a ST3 post in Plastic Surgery. Method: Data for surgical trainees progressing directly from CT2 to ST3 (2017-2019) in all specialties was obtained from the GMC. The percentage of those directly progressing that obtained a Plastic Surgery NTN and the total number progressing was calculated. Results: A total of 840 trainees obtained a NTN directly from CT2 between 2017 and 2019, 61 of whom did so in plastic surgery. Of those directly progressing, there was no significant difference between deaneries for the percentage of plastic surgery posts obtained. The highest number of trainees progressed from London deaneries (16 total (26%); 7 South, 6 NC&E, 3 NW) and the lowest number from Yorkshire and Humber (1). Conclusions: Higher numbers of those undertaking core surgical training in London progress directly from CT2 to ST3 in Plastic Surgery. Low total numbers highlight the competitive nature of obtaining a Plastic Surgery NTN, necessitating many to undertake additional experience prior to obtaining a training number.